Production improvement in an aircraft manufacturing company using value stream mapping approach - Wahab, Md Saidin (Trans Tech Publications Inc, 2014)
The purpose of this study is to develop a value stream mapping for a production in an aircraft manufacturing company. The process begins with creating a current state map and understands the production flow and the current cycle times. This provides the information needed to produce a future state map. The goal is to identify and eliminate the waste, which is any activity that does not add value to the final product, in the production process. In order to collect the information needed, the study was conducted within the production facility to enable the researcher gained knowledge and familiarized with the production flow and the activities being performed at the shop floor. Parameters such as cycle times, down times, work in process (WIP) for inventory and material, and information flow paths were recorded. This information will enable the researcher to visualize the current state of the process activities by mapping the material and information flow and looking for opportunities to eliminate wastes. ARENA simulation software package was used to simulate and analyze the process flow and times. Result from the analysis shows that there are areas where the company can further improve their production system. The results show the improvement of the cycle time up to 22% based on the new proposed arrangement of the layout. Therefore the propose layout will be guided to the company in order to improve their production.